Modulation of Campylobacter jejuni adhesion to biotic model surfaces by fungal lectins and protease inhibitors - Jug, Blaž; Šikić Pogačar, Maja; Sterniša, Meta; Tumpej, Tadeja; Karničar, Katarina; Turk, Dušan; Langerholc, Tomaž; Sabotič, Jerica; Klančnik, Anja (Frontiers in Cellular and Infection Microbiology, 2024)
Campylobacter jejuni, a Gram-negative bacterium, is one of the most common causes of foodborne illness worldwide. Its adhesion mechanism is mediated by several bacterial factors, including flagellum, protein adhesins, lipooligosaccharides, proteases, and host factors, such as surface glycans on epithelial cells and mucins. Fungal lectins, specialized carbohydrate-binding proteins, can bind to specific glycans on host and bacterial cells and thus influence pathogenesis. In this study, we investigated the effects of fungal lectins and protease inhibitors on the adhesion of C. jejuni to model biotic surfaces (mucin, fibronectin, and collagen) and Caco-2 cells as well as the invasion of Caco-2 cells. The lectins Marasmius oreades agglutinin (MOA) and Laccaria bicolor tectonin 2 (Tec2) showed remarkable efficacy in all experiments. In addition, different pre-incubations of lectins with C. jejuni or Caco-2 cells significantly inhibited the ability of C. jejuni to adhere to and invade Caco-2 cells, but to varying degrees. Pre-incubation of Caco-2 cells with selected lectins reduced the number of invasive C. jejuni cells the most, while simultaneous incubation showed the greatest reduction in adherent C. jejuni cells. These results suggest that fungal lectins are a promising tool for the prevention and treatment of C. jejuni infections. Furthermore, this study highlights the potential of fungi as a rich reservoir for novel anti-adhesive agents.